The interpretation of kinetic data for enzyme-catalysed reactions involving three substrates - Keith Dalziel (1969)
The analysis and interpretation of initial-rate data for reactions involving three substrates, obtained in suitably designed experiments, are discussed. Possible mechanisms for such reactions are classified, the rate equations are compared and the extent to which they can be distinguished experimentally is considered.